Electronic regulation and core-shell hybrids engineering of palm-leaf-like NiFe/Co(PO3)2 bifunctional electrocatalyst for efficient overall water splitting. (1st August 2022) - Gu, Fei; Zhang, Qing; Chen, Xiao Hui; Li, Ting; Fu, Hong Chuan; Luo, Hong Qun; Li, Nian Bing
Abstract: Constructing efficient and stable bifunctional electrocatalysts for overall water splitting remains a challenge because of the sluggish reaction kinetics. Herein, the core-shell hybrids composed of Co(PO3 )2 nanorod core and NiFe alloy shell in situ grown on nickel foam (NiFe/Co(PO3 )2 @NF) are synthesized. Owing to the hierarchical palm-leaf-like structures and strong adhesion between NiFe alloys, Co(PO3 )2 and substrates, the catalyst provides a large surface area and rapid charge transfer, which facilitates active sites exposure and conductivity enhancement. The interfacial effect in the NiFe/Co(PO3 )2 core-shell structure modulates the electronic structure of the active sites around the boundary, thereby boosting the intrinsic activity. Benefiting from the stable structure, the durability of the catalyst is not impaired by the inevitable surface reconfiguration. The NiFe/Co(PO3 )2 @NF electrode presents a low cell voltage of 1.63 V to achieve 10 mA cm −2 and manifests durability for up to 36 h at different current densities. Graphical abstract: The palm-leaf-like NiFe/Co(PO3 )2 @NF electrocatalyst composed of nanorod arrays serves as bifunctional electrocatalyst for enhanced overall water splitting performance. Image 1 Highlights: Strong interaction between NiFe and Co(PO3 )2 enhances the structural stability. The core-shell structure accelerates the electron transfer. The hierarchical palm-leaf-like structure helps to enlarge specific surface area. The NiFe/Co(PO3 )2 hybrids display outstanding overall water splitting activity.